Relación entre la eficiencia del área de tesorería y el desempeño de los pagos a proveedores de la Oficina Nacional de Procesos Electorales – sede Loreto 2022 - Campos Maguiña de Lima, Cheril Liuly (2023)
The payment process to suppliers by agencies is one of the public activities that generates various problems, as far as suppliers are concerned, the additional cost of paying interest to affected suppliers is uncomfortable and distrustful due to the long time they have to wait for payments to be made. On the other hand, the ONPE has obtained good results with the implementation of the new process for handling events, it has also been adapted to the needs of the market and certified for quality improvement. However, it is not exempt from deficiencies such as the functioning of the administration in terms of payments to suppliers. In this, the objective of the present work was to determine the relationship between the efficiency of the treasury area and the direction of payments to suppliers of the national office of electoral processes - LORETO headquarters, in the period 2022. For this, an investigation was carried out of a non-experimental nature, of a quantitative type and of a correlational design and it was found that there is a relationship or correlation between the variables that represent the efficiency of the treasury area and the performance of the payment of suppliers of the national office of electoral processes of the headquarters of Loreto, during the 2022 period, this connection is positive and of high magnitude, specifically, both variables are correlated by 89%.